Sea level higher than present 3500 years ago on the northern main Hawaiian Islands - Grossman, E. E.; Fletcher, C. H. (Geology, 1998)
New data from an emerged coastal bench and associated fossil beach on Kapapa Island (Oahu), Hawaii, preserve a detailed history of middle to late Holocene sea level. These include 29 new calibrated radiocarbon ages and elevations indicating mean sea level reached a maximum position of 2.00 +/- 0.35 m ca. 3500 yr B.P. These results correlate with additional evidence from Hawaii and other Pacific islands and provide constraints on Oahu's long-term uplift rate (0.03-0.07 mm/yr), previously based solely on Pleistocene age shorelines. Our sea-level reconstruction is consistent with geophysical model predictions of Earth's geoid response to the last deglaciation and with observations of increased Antarctic ice volume during the late Holocene.
Zg996Times Cited:34Cited References Count:25